Simple promotion of Cas9 and Cas12a expression improves gene targeting via an all-in-one strategy - Cheng, Yiqiu; Zhang, Lei; Li, Jing; Dang, Xiaofei; Zhu, Jian-Kang; Shimada, Hiroaki; Miki, Daisuke (Frontiers in Plant Science, 2024)
Gene targeting (GT) is a promising tool for precise manipulation of genome sequences, however, GT in seed plants remains a challenging task. The simple and direct way to improve the efficiency of GT via homology-directed repair (HDR) is to increase the frequency of double-strand breaks (DSBs) at target sites in plants. Here we report an all-in-one approach of GT in Arabidopsis by combining a transcriptional and a translational enhancer for the Cas expression. We find that facilitating the expression of Cas9 and Cas12a variant by using enhancers can improve DSB and subsequent knock-in efficiency in the Arabidopsis genome. These results indicate that simply boosting Cas protein expression at certain timings (egg cell and early embryo) can improve the establishment of these heritable GTs. This simple approach allows for routine genome engineering in plants.